Estabilidad térmica en endoperoxidos en solución: Ascaridol - Jeandupex, Rene (2002)
The importance of cyclic peroxides as the substituted I ,2,4-trioxanes, 1,2,4,5-tetroxanes and endoperoxides has grown considerably in recent years ever since the naturally occurring trioxanc artemisinine and some of its dcrivatives achievcd prominence as potent antimalarial agents. Physical properties reported for ascaridole, a cyclic endoperoxide isolated from the vegetal named Paico and also from synthetic procedures by photoxygenation of a-tcrpinene, are significantly differents. This lead lo perform the preparation of that substance by Schenck's method, but working al OºC and doing its separalion and purification al room tcmperature by preparative column chromatography .. Excelcnt yields of ascaridol were obtained (ca. 80 % GCFID) of high degree of purity (>98 %, GC; RPHPLC; NMR, 1H, 13C). The thermal stability of ascaridole in solution is advanced, reporting the activation parameters values for the unimolecular decomposition of that substance in isopropyl alcohol.